Language, Categories, and Social Reality - Lee, Zosimo E. (Social Science Diliman: A Philippine Journal of Society and Change; Vol 2 No 2 (2001), 2007)
This paper considers how awareness of concepts, categories, and criteria in language can be utilized in understanding the grammar of social institutions. The discussion then looks into how three key notions (agentive-function, collective intentionality, and the distinction between constitutive and regulative rules) not only provide clues as to how social institutions can be understood, but also provide the bases for interventions on social institutions. The development and crystallization of collective intentionality, through community deliberations, is important.